2019
DOI: 10.1111/iju.13932
|View full text |Cite
|
Sign up to set email alerts
|

Tadalafil improves bladder dysfunction and object recognition in rats with pelvic venous congestion

Abstract: Objectives To examine the effects of tadalafil on bladder function and object recognition ability in rats with alterations in urinary frequency and locomotor activity as a result of pelvic venous congestion. Methods A total of 48 female rats were divided into three groups (sham, pelvic venous congestion and pelvic venous congestion/tadalafil groups). In the pelvic venous congestion and pelvic venous congestion/tadalafil groups, the bilateral common iliac veins and uterine veins were ligated under anesthesia. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
6
1
Order By: Relevance
“…Editorial Comment to Tadalafil improves bladder dysfunction and object recognition in rats with pelvic venous congestion Nishijima et al investigated the effects of tadalafil on bladder function and object recognition ability in pelvic venous congestion (PC) rats. 1 They showed that tadalafil improved bladder function by increasing blood flow to the bladder, and by increasing the plasma dopamine levels in PC rats. Interestingly, the PC rats showed low locomotor activity and object recognition compared with the normal rats.…”
Section: Editorial Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Editorial Comment to Tadalafil improves bladder dysfunction and object recognition in rats with pelvic venous congestion Nishijima et al investigated the effects of tadalafil on bladder function and object recognition ability in pelvic venous congestion (PC) rats. 1 They showed that tadalafil improved bladder function by increasing blood flow to the bladder, and by increasing the plasma dopamine levels in PC rats. Interestingly, the PC rats showed low locomotor activity and object recognition compared with the normal rats.…”
Section: Editorial Commentmentioning
confidence: 99%
“…Nishijima et al . investigated the effects of tadalafil on bladder function and object recognition ability in pelvic venous congestion (PC) rats . They showed that tadalafil improved bladder function by increasing blood flow to the bladder, and by increasing the plasma dopamine levels in PC rats.…”
mentioning
confidence: 99%
“…In a study published in 2019 Tadalafil improved bladder function in rats with pelvic venous congestion. However, this requires further study [ 85 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Image segmentation is often used to extract the informative parts from an image that are used for further analysis or understanding. This is an essential tool in computer image analysis, computer vision, medical imaging, image identification, and image classification [1][2][3][4][5][6]. In the past decades, numerous models have been proposed for image segmentation, including thresholding [7][8][9], clustering [10,11], and active contour models (ACMs) [12,13].…”
Section: Introductionmentioning
confidence: 99%